Synthesis and Characterization of Some Transition Metal Complexes with a New2-(1,2-dihydroxyethyl-1-(2-mercaptophenyl)-5-(2 mercaptophenylimino)-2,5-dihydro-1H-pyrrol-3,4- diol. - A. Al-Najjar, Nada; H.Mousa, Falih; A. Shanshal, Muthana (Iraqi Journal of Science, 2023)
2-(1,2-dihydroxy ethyl -1- (2-mercaptophenyl)-5-(2-mercaptophenyl imino)-2,5-dihydro-1H-pyrrol-3,4-diol(H2L`)a lactam derivative of L-ascorbic acid was prepared by reaction of 5,6-O-isopropylidene L-ascorbic acid with 2-amino thiophenol in a mole ratio of (1:2) respectinely. A series of new metal complexes of this ligand (H2L`) were prepared by a reaction with the chlorides of Cr(III), Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II). The new ligand and its metal complexes were characterized by C.H.N.,1H and 13C NMR, IR as well as UV-Visible spectra and mass spectra of Ni(II) and Zn(II) complexes was also done. Atomic absorption of the metal percentage, electrical conductivity and magnetic measurements at room temperature was carried out. From these analysis showed that the ligand H2L` (C18H18O4N2S2) is coordinated to the metal ions through the nitrogen atom of the azomethine group and the two sulphur atoms of thiol groups as a tridentate ligand or through the two sulphur atoms of thiol groups as a bidentate ligand an octahedral geometries, except the (Hg) complex which shows a tetrahedral. Theoretical calculations of the electronic structure of the new ligand HL and its metal complexes were carried out applying the semi-emiprical computation methods PM3 and PM6 which confirmed the suggested structures of all complexes.